HUBUNGAN USIA IBU, KETUBAN PECAH DINI DAN PARITAS DENGAN KEJADIAN ASFIKSIA PADA BAYI BARU LAHIR DI RSUD KAYU AGUNG KABUPATEN OKI - Gina Sari; Murdiningsih; Putu Lusita Nati Indriani (Jurnal Kesehatan dan Pembangunan, 2024)
Asphyxia in newborns is a serious problem in Indonesia because the infant mortality rate due to asphyxia is still quite high. Neonatal asphyxia is the failure of the baby to breathe spontaneously and regularly at birth or some time after birth which is characterized by hypoxemia, hypercarbia and acidosis. The formulation of the problem this study there is a relationship between maternal age, premature rupture of membranes and parity simultaneously with the incidence of asphyxia in newborns. This study aims to determine the relationship between maternal age, premature rupture of membranes and parity with the incidence of asphyxia in newborns. The conceptual framework of this research is the independent variable (maternal age, premature rupture of membranes and parity) while the dependent variable (incidence of asphyxia) and the research hypothesis is to determine the relationship between maternal age, premature rupture of membranes and parity with the incidence of asphyxia in newborns. This study used a case control design on 90 samples with 30 case samples and 60 control samples with a purposive sampling technique. The analysis used is univariate and bivariate with chi square. The results of the study showed that there was a relationship between maternal age p value (0.015), premature rupture of membranes p value (0.000) and parity p value (0.021) with the incidence of asphyxia in newborns. Suggestion of this research this can be used as a reference material and for evaluating policies related to neonatal asphyxia as an effort to prevent and reduce infant mortality (IMR).